EP866 Prognostic and predictive implication of hormonal receptors expression and tumor infiltrating lymphocyte in epithelial ovarian cancer. (1st November 2019) - Kim, J-H; Han, GH; Chay, DB; Cho, H; Kim, S
Abstract : Introduction/Background: The effect of systemic treatment depends on the subtypes classified by hormone receptors in breast cancer. However, the effect of hormone receptor status in epithelial ovarian cancer (EOC) is still unclear. Therefore, here we assessed the clinical implication of the hormone receptor status and association with TILs in patients of EOC. Methodology: Immunohistochemical analysis of estrogen receptor α (ER α), estrogen receptor β (ER β), progesterone receptor (PR), androgen receptor (AR) and glucocorticoid receptor (GR), CD4+ and CD8+ were performed by using tissue microarray analysis of 358 ovarian tumors and the data were compared with clinicopathological variables, including the survival. Cluster analysis was perfored to identify the subgroups by hormone receptor. Receptor expression and correlation with TIL was correlated to uni- and multivariate analysis. Results: Using cox proportional hazards model, high expression of ER α, ER β and low expression of AR, GR and PR, a combined AR/ER α expression [HR=3.25 (95% CI: 1.56–6.98), p =0.003] and a combined GR/ER α expression [HR=1.93 (95% CI: 1.01–3.68), p =0.046] were revealed to be a poor prognostic subtypes. Also clustering analysis revealed subgroup with hormone receptor ER α positive disease had poor DFS and OS. Finally, in the association between CD4/CD8 and AR-/ER α+ and GR-/ER α+ were analyzed by cox proportional hazards model. The increased of CD4/CD8 was associated with longer overall survival (OS) in AR -/ER α+ and GR-/ER α+ subtypes [HR=1.95 (95% CI: 1.02–3.73), p =0.041]. Conclusion: In conclusion, increased CD4+ and CD8+ TIL infiltration correlated with improved survival in the whole subtypes as well as in poor prognostic subtypes, AR-/ER α+ and GR-/ER α+ in EOC. Thus, assessment of these TILs in EOC is essential, and their clinical prognostic implications should be considered according to hormone receptor status. Disclosure: Nothing to disclose.